Epigenetic Regulation of Host Defense Peptide Synthesis: Synergy Between Histone Deacetylase Inhibitors and DNA/Histone Methyltransferase Inhibitors - Whitmore, Melanie A.; Li, Hong; Lyu, Wentao; Khanam, Sharmily; Zhang, Guolong (Frontiers in Immunology, 2022)
Host defense peptides (HDPs) are an integral part of the innate immune system as the first line of defense against infections. Modulation of HDP synthesis has emerged as a promising host-directed approach to fight against infections. Inhibition of histone deacetylation or DNA methylation has been found to enhance HDP gene expression. In this study, we explored a possible synergy in HDP gene induction between histone deacetylase inhibitors (HDACi) and DNA/histone methyltransferase inhibitors (DNMTi/HMTi). Chicken macrophage cells were treated with structurally distinct HDACi, HMTi, or DNMTi individually or in combination, followed by HDP gene expression analysis. Each epigenetic compound was found to be capable of inducing HDP expression. To our surprise, a combination of HDACi and HMTi or HDACi and DNMTi showed a strong synergy to induce the expressions of most HDP genes. The HDP-inducing synergy between butyrate, an HDACi, and BIX01294, an HMTi, were further verified in chicken peripheral blood mononuclear cells. Additionally, tight junction proteins such as claudin 1 were also synergistically induced by HDACi and HMTi. Overall, we concluded that HDP genes are regulated by epigenetic modifications. Strategies to increase histone acetylation while reducing DNA or histone methylation could exert a synergistic effect on HDP induction and, therefore, have potential for the control and prevention of infectious diseases.